Association Between Herd Size and the Chemical Composition and Technological Properties of Milk Intended for Parmigiano Reggiano PDO Cheese - Piero Franceschi; Paolo Formaggioni; Davide Barbanti; Yesid Orlando Gonzalez Torres; Cristina Scotti; Francesca Martuzzi (Foods, 2025)
The aim of this research was to compare the chemical composition and the technological characteristics of milk for Parmigiano Reggiano cheese produced in herds with different numbers of cows. The research was carried out on 5760 Italian Friesian herd milk samples collected from a total of 160 farms (one sample per month in each farm for three years). On each milk sample, lactose, fat, protein, casein, titratable acidity, total bacterial count, somatic cells, coliform bacteria, clostridia spores, and rennet coagulation properties were determined. Increasing herd size was positively correlated with milk production and with milk somatic cell and clostridia spores’ contents (8133 kg/cow/lactation, 5.280 Log10cells/mL and 1.782 spores/L for herds with less than 30 cows; 9109 kg/cow/lactation, 5.548 Log10cells/mL and 2.138 spores/L for herds with more than 200 cows, respectively). Moreover, herd size was negatively correlated with milk fat content and with total bacterial and coliform bacteria counts (3.73 g/100 g, 4.931 Log10CFU/mL and 3.176 Log10CFU/mL for herds with less than 30 cows; 3.51 g/100 g, 4.770 Log10CFU/mL and 3.121 Log10CFU/mL for herds with more than 200 cows, respectively). Farms with more than 100 cows raised were characterised by higher milk production per cow per lactation, but the milk produced by them was also characterised by lower fat content. Finally, milk produced in the herds with a higher number of cows showed a higher frequency of optimal lactodynamographic types (better rennet-coagulation properties) than milk produced in the other herds.